A method for preparing high-strength alumina-based porcelain insulator
Through specific raw material ratios and complex process steps, high-strength alumina-based porcelain insulators are prepared, solving the shortcomings of existing insulator materials in terms of high strength and electrical breakdown resistance, and achieving efficient insulation performance improvement.
Patent Information
- Application Number
- CN202410260905.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-03-07
AI Technical Summary
The existing insulator materials have shortcomings in high strength and electrical breakdown resistance, which is difficult to meet the needs of modern transmission lines to improve insulation performance.
Using a high-strength alumina-based porcelain insulator, through specific raw material ratios and preparation processes, including the use of industrial alumina powder, reinforced powder, Anyuan clay and other raw materials, and through complex process steps such as electrospinning, multiple times Immerse and copper plating by tetrabutyl zirconate to prepare an alumina-based ceramic body with high strength and electrical breakdown resistance.
It realizes the high bending strength and electrical breakdown resistance of alumina-based porcelain insulators, can withstand large load forces, is not easy to damage, and improves insulation performance and enhances the safety of insulators during use.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulator materials, and in particular to a method for preparing a high-strength alumina-based porcelain insulator. Background Art
[0002] Electricity is the most widely used secondary energy in modern society. The safe, stable operation and sufficient supply of electricity are important guarantees for the sustainable development of the national economy. Today's transmission lines are divided into two categories: one is underground cables and the other is overhead lines. Overhead lines are transmission lines that suspend bare wires (now insulated wires) on supporting towers with insulators. Overhead transmission lines have simple structures and equipment, are easy to manufacture and supply, have low costs, are easy to construct, and are fast to build, so that economic benefits can be harvested early. Moreover, most of the facilities are exposed to the surface, which is convenient for operation and maintenance. Therefore, overhead transmission lines are widely used at home and abroad.
[0003] Insulators are the most widely used components in power transmission and transformation projects. They are divided into porcelain insulators, composite insulators and glass insulators according to different materials. Among them, porcelain insulators belong to traditional insulators, which are mainly composed of four parts, namely steel cap, cement adhesive, porcelain body and connection hardware, among which the porcelain body is the main insulating component. Summary of the invention
[0004] The present invention provides a high-strength alumina-based porcelain insulator, comprising an alumina-based porcelain body, wherein the raw materials of the alumina-based porcelain body include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, and the preparation method of the reinforcing powder is:
[0005] (1) preparing an aqueous solution of acetic acid; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and continuing to keep the solution at 90±3° C. and stirring for 5 to 6 hours after the addition is completed, and condenses and refluxes during the insulation process; cooling to 50±3° C. and keeping the solution under stirring after the insulation is completed, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution under stirring, keeping the solution at 50±3° C. and stirring for more than 1 hour after the addition is completed, and then rotary evaporating at 50° C. and concentrating the solution to a viscosity of 1 to 2 Pa·s, and then performing electrostatic spinning to obtain gel fibers; the gel fibers are first heated to 700 to 750° C. and calcined for 50 to 60 minutes, and then heated to 1150 to 1170° C. and calcined for 60 to 80 minutes, and after the calcination is completed, air-cooling to room temperature to obtain reinforced fibers;
[0006] (2) preparing an ethanol solution of tetrabutyl zirconate, immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for more than 10 minutes, then separating the solid and the liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing it in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a group of processes as a whole, and the above-mentioned processes are repeated for a total of 10 groups, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber;
[0007] (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, then immersing the zirconium oxide layer-coated fiber in the aqueous solution of stannous chloride, stirring the solution for 10 to 12 minutes, then separating the solid from the liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the fiber in the aqueous solution of silver nitrate for 10 to 12 minutes, separating the solid from the liquid after immersion, and drying the solid phase at 80° C. for 10 minutes to obtain a pretreated solid phase; preparing a copper plating solution, keeping the copper plating solution constant at 60±2° C. in a water bath, then immersing the pretreated solid phase in the copper plating solution, immersing the fiber at 60±2° C. for 15 to 18 minutes, then separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, calcining the solid phase in a muffle furnace at 300° C. for 20 to 30 minutes, and then air cooling the solid phase to room temperature to obtain the reinforced powder.
[0008] Furthermore, the raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 10-12 parts of reinforcing powder, 8-15 parts of Anyuan clay; 4-6 parts of potassium feldspar; 4-6 parts of titanium dioxide; 2-3 parts of boric acid; 2-4 parts of phosphorus pentoxide; 3-6 parts of kaolin; and 1-3 parts of diatomaceous earth.
[0009] Furthermore, in the step (1), the mass percentage of acetic acid in the aqueous solution of acetic acid is 20%, and the solvent is water; the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6 to 7:100; the mass ratio of silica sol, cerium nitrate and polyvinyl alcohol added to the solution and the mass ratio of magnesium hydroxide added is magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 6 to 7:10: 3 to 4: 3 to 5; wherein the mass percentage of the solute in the silica sol is 20%.
[0010] Furthermore, in the step (2), in the ethanol solution of tetrabutyl zirconate, the mass percentage of tetrabutyl zirconate is 5%, and the solvent is ethanol; the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50.
[0011] Furthermore, in the step (3), in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; the solid-liquid mass ratio of the zirconium oxide layer coated fiber immersed in the aqueous solution of stannous chloride is zirconium oxide layer coated fiber: aqueous solution of stannous chloride = 1:50; the solid-liquid mass ratio of the dried solid phase immersed in the aqueous solution of silver nitrate is dried solid phase: aqueous solution of silver nitrate = 1:50.
[0012] Furthermore, the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10 g / L, the concentration of potassium sodium tartrate is 38 g / L, the concentration of formaldehyde is 17 mL / L, and the solvent is water.
[0013] The present invention also discloses a method for preparing the alumina-based ceramic body, comprising:
[0014] Step 1, weighing each raw material component according to the weight proportion, preparing an aqueous solution of ammonium citrate, then adding the reinforcing powder to the aqueous solution of ammonium citrate, stirring the solution for more than 20 minutes, then adding sodium alginate and other raw material components to the solution, stirring the mixture for more than 30 minutes to mix evenly, adjusting the water content to 20%, and die-casting to obtain a blank;
[0015] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based ceramic body.
[0016] Furthermore, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, and the mass of sodium alginate added is 1 / 10 of the mass of industrial alumina powder in the raw material components.
[0017] The beneficial effects of the present invention are as follows: the reinforcing powder of the present invention is added to the alumina matrix ceramic, which can change the anisotropic liquid-solid interface energy of the alumina matrix during the sintering process, thereby reducing the free energy of the matrix grain boundary, effectively inhibiting the abnormal growth of the alumina matrix grains, and playing a certain fine grain strengthening effect. At the same time, it helps to homogenize the ceramic structure and reduce the problems of weak local strength and insulation of the ceramic. On the other hand, the formed Cu-Zr oxide surface layer makes the reinforcing powder more tightly combined with the alumina matrix, and can inhibit the abnormal growth of the alumina matrix grains and the generation of microcracks in the pore wall during the sintering process, so as to achieve the purpose of improving the strength. The alumina-based ceramic body prepared by the method of the present invention has good bending strength and electrical breakdown resistance, can withstand large load forces, and is not easy to be damaged; and has high insulation performance, which improves the safety of the insulator during use. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the embodiments.
[0019] Example 1
[0020] A high-strength alumina-based porcelain insulator includes an alumina-based porcelain body, the raw materials of which include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, and each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 10 parts of reinforcing powder, 8 parts of Anyuan clay; 4 parts of potassium feldspar; 4 parts of titanium dioxide; 2 parts of boric acid; 2 parts of phosphorus pentoxide; 3 parts of kaolin; 1 part of diatomaceous earth. The preparation method of the reinforcing powder is:
[0021] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6:100; after the addition is completed, the solution is kept at 90±3° C. and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm, and silica sol and nitric acid are added to the solution under stirring after the insulation. Cerium and polyvinyl alcohol, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution and adding magnesium hydroxide in a mass ratio of magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 6:10:3:3; wherein the mass percentage of the solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0022] (2) preparing an ethanol solution of tetrabutyl zirconate, wherein the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for 10 minutes, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50; then separating the solid and liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, and then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a set of processes as a whole, and the above-mentioned processes are repeated for a total of 10 sets, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber;
[0023] (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, and then immersing the zirconium oxide layer coated fiber in the aqueous solution of stannous chloride, wherein the solid-liquid mass ratio of the zirconium oxide layer coated fiber to the aqueous solution of stannous chloride is 1:50; keeping the solution warm and stirring for 10 minutes, and then separating the solid and liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes, and immersing the dried solid phase in The solid-liquid mass ratio of the silver nitrate aqueous solution is the solid phase after drying: the silver nitrate aqueous solution = 1:50; after the immersion is completed, the solid-liquid separation is performed, and the solid phase is dried at 80°C for 10 minutes to obtain a pretreated solid phase; a copper plating solution is prepared, and the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10g / L, the concentration of potassium sodium tartrate is 38g / L, the concentration of formaldehyde is 17mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2°C in a water bath, and then the pretreated solid phase is immersed in the copper plating solution, and immersed at a constant temperature of 60±2°C for 15 minutes, and then the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and placed in a muffle furnace at 300°C for calcination for 25 minutes, and then air-cooled to room temperature to obtain the reinforced powder.
[0024] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0025] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0026] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample.
[0027] Example 2
[0028] A high-strength alumina-based porcelain insulator includes an alumina-based porcelain body, the raw materials of which include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, and each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 11 parts of reinforcing powder, 10 parts of Anyuan clay; 5 parts of potassium feldspar; 5 parts of titanium dioxide; 2 parts of boric acid; 3 parts of phosphorus pentoxide; 4 parts of kaolin; and 2 parts of diatomaceous earth. The preparation method of the reinforcing powder is:
[0029] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6:100; after the addition is completed, the solution is kept at 90±3° C. and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm, and silica sol and nitric acid are added to the solution under stirring after the insulation. Cerium and polyvinyl alcohol, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution and adding magnesium hydroxide in a mass ratio of magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 6:10:3:4; wherein the mass percentage of the solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0030] (2) preparing an ethanol solution of tetrabutyl zirconate, wherein the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for 10 minutes, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50; then separating the solid and liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, and then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a set of processes as a whole, and the above-mentioned processes are repeated for a total of 10 sets, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber;
[0031] (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, and then immersing the zirconium oxide layer coated fiber in the aqueous solution of stannous chloride, wherein the solid-liquid mass ratio of the zirconium oxide layer coated fiber to the aqueous solution of stannous chloride is 1:50; keeping the solution warm and stirring for 10 minutes, and then separating the solid and liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes, and immersing the dried solid phase in The solid-liquid mass ratio of the silver nitrate aqueous solution is the solid phase after drying: the silver nitrate aqueous solution = 1:50; after the immersion is completed, the solid-liquid separation is performed, and the solid phase is dried at 80°C for 10 minutes to obtain a pretreated solid phase; a copper plating solution is prepared, and the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10g / L, the concentration of potassium sodium tartrate is 38g / L, the concentration of formaldehyde is 17mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2°C in a water bath, and then the pretreated solid phase is immersed in the copper plating solution, and immersed at a constant temperature of 60±2°C for 15 minutes, and then the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and placed in a muffle furnace at 300°C for calcination for 25 minutes, and then air-cooled to room temperature to obtain the reinforced powder.
[0032] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0033] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0034] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample.
[0035] Example 3
[0036] A high-strength alumina-based porcelain insulator includes an alumina-based porcelain body, the raw materials of which include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, and each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 11 parts of reinforcing powder, 12 parts of Anyuan clay; 5 parts of potassium feldspar; 5 parts of titanium dioxide; 3 parts of boric acid; 3 parts of phosphorus pentoxide; 5 parts of kaolin; 2 parts of diatomaceous earth. The preparation method of the reinforcing powder is:
[0037] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 7:100; after the addition is completed, the solution is kept at 90±3° C. and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm, and silica sol and nitric acid are added to the solution under stirring after the insulation. Cerium and polyvinyl alcohol, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution and adding magnesium hydroxide in a mass ratio of magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 7:10:4:4; wherein the mass percentage of the solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0038] (2) preparing an ethanol solution of tetrabutyl zirconate, wherein the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for 10 minutes, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50; then separating the solid and liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, and then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a set of processes as a whole, and the above-mentioned processes are repeated for a total of 10 sets, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber;
[0039] (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, and then immersing the zirconium oxide layer coated fiber in the aqueous solution of stannous chloride, wherein the solid-liquid mass ratio of the zirconium oxide layer coated fiber to the aqueous solution of stannous chloride is 1:50; keeping the solution warm and stirring for 10 minutes, and then separating the solid and liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes, and immersing the dried solid phase in The solid-liquid mass ratio of the silver nitrate aqueous solution is the solid phase after drying: the silver nitrate aqueous solution = 1:50; after the immersion is completed, the solid-liquid separation is performed, and the solid phase is dried at 80°C for 10 minutes to obtain a pretreated solid phase; a copper plating solution is prepared, and the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10g / L, the concentration of potassium sodium tartrate is 38g / L, the concentration of formaldehyde is 17mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2°C in a water bath, and then the pretreated solid phase is immersed in the copper plating solution, and immersed at a constant temperature of 60±2°C for 15 minutes, and then the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and placed in a muffle furnace at 300°C for calcination for 25 minutes, and then air-cooled to room temperature to obtain the reinforced powder.
[0040] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0041] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0042] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample.
[0043] Example 4
[0044] A high-strength alumina-based porcelain insulator includes an alumina-based porcelain body, the raw materials of which include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, and each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 12 parts of reinforcing powder, 15 parts of Anyuan clay; 6 parts of potassium feldspar; 6 parts of titanium dioxide; 3 parts of boric acid; 4 parts of phosphorus pentoxide; 6 parts of kaolin; 3 parts of diatomaceous earth. The preparation method of the reinforcing powder is:
[0045] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 7:100; after the addition is completed, the solution is kept at 90±3° C. and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm, and silica sol and nitric acid are added to the solution under stirring after the insulation. Cerium and polyvinyl alcohol, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution and adding magnesium hydroxide in a mass ratio of magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 7:10:4:5; wherein the mass percentage of the solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0046] (2) preparing an ethanol solution of tetrabutyl zirconate, wherein the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for 10 minutes, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50; then separating the solid and liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, and then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a set of processes as a whole, and the above-mentioned processes are repeated for a total of 10 sets, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber;
[0047] (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, and then immersing the zirconium oxide layer coated fiber in the aqueous solution of stannous chloride, wherein the solid-liquid mass ratio of the zirconium oxide layer coated fiber to the aqueous solution of stannous chloride is 1:50; keeping the solution warm and stirring for 10 minutes, and then separating the solid and liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes, and immersing the dried solid phase in The solid-liquid mass ratio of the silver nitrate aqueous solution is the solid phase after drying: the silver nitrate aqueous solution = 1:50; after the immersion is completed, the solid-liquid separation is performed, and the solid phase is dried at 80°C for 10 minutes to obtain a pretreated solid phase; a copper plating solution is prepared, and the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10g / L, the concentration of potassium sodium tartrate is 38g / L, the concentration of formaldehyde is 17mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2°C in a water bath, and then the pretreated solid phase is immersed in the copper plating solution, and immersed at a constant temperature of 60±2°C for 15 minutes, and then the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and placed in a muffle furnace at 300°C for calcination for 25 minutes, and then air-cooled to room temperature to obtain the reinforced powder.
[0048] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0049] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0050] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample.
[0051] Comparative Example 1
[0052] A comparative alumina-based porcelain body, the raw materials of which include: industrial alumina powder, magnesium oxide powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, each of which is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 11 parts of magnesium oxide powder, 10 parts of Anyuan clay; 5 parts of potassium feldspar; 5 parts of titanium dioxide; 2 parts of boric acid; 3 parts of phosphorus pentoxide; 4 parts of kaolin; and 2 parts of diatomaceous earth.
[0053] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0054] Step 1, weighing each raw material component according to the weight proportion, preparing an aqueous solution of ammonium citrate, wherein the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then adding the magnesium oxide powder to the aqueous solution of ammonium citrate, wherein the solid-liquid mass ratio of the magnesium oxide powder added to the aqueous solution of ammonium citrate is magnesium oxide powder: aqueous solution of ammonium citrate = 1:40; stirring the solution for 20 minutes, and then adding sodium alginate and other raw material components to the solution, wherein the added mass of sodium alginate is 1 / 10 of the mass of the industrial alumina powder in the raw material components; stirring the mixture for 30 minutes to mix evenly, adjusting the water content to 20%, and die-casting to obtain a test blank and a porcelain body blank;
[0055] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample described in this comparative example.
[0056] Comparative Example 2
[0057] An alumina-based porcelain body for comparison, the raw materials of the alumina-based porcelain body include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 11 parts of reinforcing powder, 10 parts of Anyuan clay; 5 parts of potassium feldspar; 5 parts of titanium dioxide; 2 parts of boric acid; 3 parts of phosphorus pentoxide; 4 parts of kaolin; 2 parts of diatomaceous earth. The preparation method of the reinforcing powder is:
[0058] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3°C in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6:100; after the addition is completed, the solution is kept at 90±3°C and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3°C and kept warm, and after the insulation is completed, the solution is added to the solution under stirring. Add silica sol and polyvinyl alcohol, and the mass ratio of adding silica sol and polyvinyl alcohol to magnesium hydroxide is 6:10:4; the mass percentage of solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0059] (2) preparing an ethanol solution of tetrabutyl zirconate, wherein the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for 10 minutes, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50; then separating the solid and liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, and then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a set of processes as a whole, and the above-mentioned processes are repeated for a total of 10 sets, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber;
[0060] (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, and then immersing the zirconium oxide layer coated fiber in the aqueous solution of stannous chloride, wherein the solid-liquid mass ratio of the zirconium oxide layer coated fiber to the aqueous solution of stannous chloride is 1:50; keeping the solution warm and stirring for 10 minutes, and then separating the solid and liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes, and immersing the dried solid phase in The solid-liquid mass ratio of the silver nitrate aqueous solution is the solid phase after drying: the silver nitrate aqueous solution = 1:50; after the immersion is completed, the solid-liquid separation is performed, and the solid phase is dried at 80°C for 10 minutes to obtain a pretreated solid phase; a copper plating solution is prepared, and the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10g / L, the concentration of potassium sodium tartrate is 38g / L, the concentration of formaldehyde is 17mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2°C in a water bath, and then the pretreated solid phase is immersed in the copper plating solution, and immersed at a constant temperature of 60±2°C for 15 minutes, and then the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and placed in a muffle furnace at 300°C for calcination for 25 minutes, and then air-cooled to room temperature to obtain the reinforced powder.
[0061] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0062] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0063] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample described in this comparative example.
[0064] Comparative Example 3
[0065] An alumina-based porcelain body for comparison, the raw materials of the alumina-based porcelain body include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 11 parts of reinforcing powder, 10 parts of Anyuan clay; 5 parts of potassium feldspar; 5 parts of titanium dioxide; 2 parts of boric acid; 3 parts of phosphorus pentoxide; 4 parts of kaolin; 2 parts of diatomaceous earth. The preparation method of the reinforcing powder is:
[0066] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6:100; after the addition is completed, the solution is kept at 90±3° C. and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm, and silica sol and nitric acid are added to the solution under stirring after the insulation. Cerium and polyvinyl alcohol, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution and adding magnesium hydroxide in a mass ratio of magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 6:10:3:4; wherein the mass percentage of the solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0067] (2) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, and then immersing the reinforcing fiber in the aqueous solution of stannous chloride, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the aqueous solution of stannous chloride is reinforcing fiber: aqueous solution of stannous chloride = 1:50; keeping the solution warm and stirring for 10 minutes, and then separating the solid and liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes, and immersing the dried solid phase in the aqueous solution of silver nitrate for 10 minutes. The solid-liquid mass ratio in the solution is the solid phase after drying: the aqueous solution of silver nitrate = 1:50; after the immersion is completed, the solid-liquid separation is performed, and the solid phase is dried at 80°C for 10 minutes to obtain a pretreated solid phase; a copper plating solution is prepared, and the copper plating solution is a mixed aqueous solution of copper sulfate, potassium sodium tartrate, and formaldehyde, wherein the concentration of copper sulfate is 10g / L, the concentration of potassium sodium tartrate is 38g / L, the concentration of formaldehyde is 17mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2°C in a water bath, and then the pretreated solid phase is immersed in the copper plating solution, and is immersed at a constant temperature of 60±2°C for 15 minutes, and then the solid-liquid separation is performed, the solid phase is washed with deionized water 3 times, and is placed in a muffle furnace at 300°C for calcination for 25 minutes, and then air-cooled to room temperature to obtain the enhanced powder.
[0068] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0069] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0070] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample described in this comparative example.
[0071] Comparative Example 4
[0072] An alumina-based porcelain body for comparison, the raw materials of the alumina-based porcelain body include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, each raw material is a sieved powder through a 200-mesh sieve. The raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 11 parts of reinforcing powder, 10 parts of Anyuan clay; 5 parts of potassium feldspar; 5 parts of titanium dioxide; 2 parts of boric acid; 3 parts of phosphorus pentoxide; 4 parts of kaolin; 2 parts of diatomaceous earth. The preparation method of the reinforcing powder is:
[0073] (1) preparing an aqueous solution of acetic acid; in the aqueous solution of acetic acid, the mass percentage of acetic acid is 20%, and the solvent is water; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then stirring the aqueous solution of acetic acid, adding magnesium hydroxide to the solution under stirring, and the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6:100; after the addition is completed, the solution is kept at 90±3° C. and stirred for 5 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm, and silica sol and nitric acid are added to the solution under stirring after the insulation. Cerium and polyvinyl alcohol, adding silica sol, cerium nitrate and polyvinyl alcohol to the solution and adding magnesium hydroxide in a mass ratio of magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 6:10:3:4; wherein the mass percentage of the solute in the silica sol is 20%; after the addition is completed, the solution is stirred at 50±3°C for 1h, and then rotary evaporated at 50°C to concentrate the solution to a viscosity of 1Pa·s, and then electrospun to obtain gel fiber; the gel fiber is first heated to 720°C and calcined for 60min, and then heated to 1150°C and calcined for 80min, and after the calcination is completed, it is air-cooled to room temperature to obtain reinforced fiber;
[0074] (2) preparing an ethanol solution of tetrabutyl zirconate, wherein the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for 10 minutes, wherein the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:50; then separating the solid and the liquid, drying the solid phase in a drying oven at 100°C for 15 minutes, and then calcining in a muffle furnace at 500°C for 20 minutes, air-cooling to room temperature after calcination, and then immersing in the ethanol solution of tetrabutyl zirconate again; the above-mentioned immersion, solid-liquid separation, drying, calcining, and air-cooling steps are a group of processes as a whole, and the above-mentioned processes are repeated for a total of 10 groups, and the last calcination is at 500°C for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber as the reinforcing powder of this comparative example.
[0075] The method for preparing the above-mentioned alumina-based ceramic body comprises:
[0076] Step 1, weigh each raw material component according to the weight proportion, prepare an aqueous solution of ammonium citrate, the mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, then add the reinforcing powder into the aqueous solution of ammonium citrate, the solid-liquid mass ratio of reinforcing powder added into the aqueous solution of ammonium citrate is reinforcing powder: aqueous solution of ammonium citrate=1:40; stir the solution for 20 minutes, then add sodium alginate and other raw material components into the solution, the added mass of sodium alginate is 1 / 10 of the mass of industrial alumina powder in the raw material components; stir the mixture for 30 minutes to mix evenly, adjust the water content to 20%, and die-cast to obtain a test blank and a porcelain body blank;
[0077] Step 2: Heat the blank to 500°C at a rate of 10°C / min and keep it warm for 1 hour; then heat it to 1300°C at a rate of 5°C / min and keep it warm for 30 minutes; then heat it to 1500°C at a rate of 2°C / min and keep it warm for 2 hours; after the insulation is completed, cool it to room temperature at a rate of 5°C / min to obtain the alumina-based porcelain body and test sample described in this comparative example.
[0078] Example 5
[0079] The bending strength of the test specimens prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T 8411.2-2008, wherein the specimen and fixture dimensions were based on the C500 group, and the loading speed was 50 N / s. The results are shown in Table 1. The electrical breakdown strength of the test specimens prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T 1408.1-2016, and the results are shown in Table 1.
[0080] Table 1
[0081] Experimental Group Tensile strength / MPa Electrical breakdown strength (kV / mm) Example 1 196 38.07 Example 2 207 38.24 Example 3 204 38.33 Example 4 201 38.18 Comparative Example 1 142 31.59 Comparative Example 2 183 33.46 Comparative Example 3 168 33.05 Comparative Example 4 161 32.82
[0082] It can be seen from Table 1 that the alumina-based porcelain body prepared by the method of the present invention has good bending strength and electrical breakdown strength, can withstand a large load force, and is not easily damaged; and has high insulation performance, which improves the safety of the insulator during use.
[0083] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A high-strength alumina-based porcelain insulator, characterized in that: The invention comprises an alumina-based porcelain body, wherein the raw materials of the alumina-based porcelain body include: industrial alumina powder, reinforcing powder, Anyuan clay, potassium feldspar, titanium dioxide, boric acid, phosphorus pentoxide, kaolin and diatomaceous earth, wherein the raw material components are calculated by weight as follows: 50 parts of industrial alumina powder; 10-12 parts of reinforcing powder, 8-15 parts of Anyuan clay; 4-6 parts of potassium feldspar; 4-6 parts of titanium dioxide; 2-3 parts of boric acid; 2-4 parts of phosphorus pentoxide; 3-6 parts of kaolin; 1-3 parts of diatomaceous earth; and the preparation method of the reinforcing powder is as follows: (1) preparing an aqueous solution of acetic acid; the aqueous solution of acetic acid is kept at a constant temperature of 90±3° C. in a water bath, and condenses and refluxes during the insulation process; then the aqueous solution of acetic acid is stirred, and magnesium hydroxide is added to the solution under stirring. After the addition is completed, the solution is kept at 90±3° C. and stirred for 5 to 6 hours, and condenses and refluxes during the insulation process; after the insulation is completed, the solution is cooled to 50±3° C. and kept warm. After the insulation is completed, silica sol, cerium nitrate and polyvinyl alcohol are added to the solution under stirring. After the addition is completed, the solution is kept at 50±3° C. and stirred for more than 1 hour, and then rotary evaporated at 50° C. and concentrated to a solution viscosity of 1 to 2 Pa·s, and then electrospun to obtain gel fibers; the gel fibers are first heated to 700 to 750° C. and calcined for 50 to 60 minutes, and then heated to 1150 to 1170° C. and calcined for 60 to 80 minutes. After the calcination is completed, the solution is air-cooled to room temperature to obtain reinforced fibers; (2) preparing an ethanol solution of tetrabutyl zirconate, immersing the reinforcing fiber in the ethanol solution of tetrabutyl zirconate for more than 10 minutes, then separating the solid and the liquid, drying the solid phase in a drying oven at 100° C. for 15 minutes, then calcining in a muffle furnace at 500° C. for 20 minutes, air-cooling to room temperature after calcination, and then immersing it in the ethanol solution of tetrabutyl zirconate again; the above immersion, solid-liquid separation, drying, calcination, and air-cooling steps are a set of processes as a whole, and the above processes are repeated for a total of 10 sets, and the last calcination is at 500° C. for 2 hours, and then air-cooling to room temperature to obtain a zirconium oxide layer coated fiber; (3) preparing an aqueous solution of stannous chloride and an aqueous solution of silver nitrate; keeping the aqueous solution of stannous chloride constant at 30±2° C. in a water bath, then immersing the zirconium oxide layer-coated fiber in the aqueous solution of stannous chloride, stirring the solution for 10 to 12 minutes, then separating the solid from the liquid, and drying the solid phase at 80° C. for 10 minutes; after drying, immersing in the aqueous solution of silver nitrate for 10 to 12 minutes, separating the solid from the liquid after immersion, and drying the solid phase at 80° C. for 10 minutes to obtain a pretreated solid phase; preparing a copper plating solution, wherein the copper plating solution is copper sulfate , potassium sodium tartrate, and formaldehyde in a mixed aqueous solution, wherein the concentration of copper sulfate is 10 g / L, the concentration of potassium sodium tartrate is 38 g / L, the concentration of formaldehyde is 17 mL / L, and the solvent is water; the copper plating solution is kept at a constant temperature of 60±2° C. in a water bath, and then the pretreated solid phase is immersed in the copper plating solution at a constant temperature of 60±2° C. for 15 to 18 min, and then the solid-liquid is separated, the solid phase is washed with deionized water for more than 3 times, and placed in a muffle furnace at 300° C. for calcination for 20 to 30 min, and then air-cooled to room temperature to obtain the reinforced powder.
2. A high-strength alumina-based porcelain insulator according to claim 1, characterized in that: In the step (1), the mass percentage of acetic acid in the aqueous solution of acetic acid is 20%, and the solvent is water; the mass ratio of magnesium hydroxide added to the solution is magnesium hydroxide: acetic acid aqueous solution = 6-7:100; the mass ratio of silica sol, cerium nitrate and polyvinyl alcohol added to the solution and the mass ratio of magnesium hydroxide added is magnesium hydroxide: silica sol: cerium nitrate: polyvinyl alcohol = 6-7:10:3-4:3-5; wherein the mass percentage of the solute in the silica sol is 20%.
3. A high-strength alumina-based porcelain insulator according to claim 1, characterized in that: In the step (2), the mass percentage of tetrabutyl zirconate in the ethanol solution of tetrabutyl zirconate is 5%, and the solvent is ethanol; the solid-liquid mass ratio of the reinforcing fiber immersed in the ethanol solution of tetrabutyl zirconate is reinforcing fiber: ethanol solution of tetrabutyl zirconate = 1:
50.
4. A high-strength alumina-based porcelain insulator according to claim 1, characterized in that: In the step (3), in the aqueous solution of stannous chloride, the concentration of stannous chloride is 10 g / L, and the solvent is water; in the aqueous solution of silver nitrate, the concentration of silver nitrate is 16 g / L, and the solvent is water; the solid-liquid mass ratio of the zirconium oxide layer coated fiber immersed in the aqueous solution of stannous chloride is zirconium oxide layer coated fiber: aqueous solution of stannous chloride = 1:50; the solid-liquid mass ratio of the dried solid phase immersed in the aqueous solution of silver nitrate is dried solid phase: aqueous solution of silver nitrate = 1:
50.
5. A high-strength alumina-based porcelain insulator as claimed in claim 1, characterized in that: The preparation method of the alumina-based porcelain body is as follows: Step 1, weighing each raw material component according to the weight proportion, preparing an aqueous solution of ammonium citrate, then adding the reinforcing powder to the aqueous solution of ammonium citrate, stirring the solution for more than 20 minutes, then adding sodium alginate and other raw material components to the solution, stirring the mixture for more than 30 minutes to mix evenly, adjusting the water content to 20%, and die-casting to obtain a blank; Step 2: Raise the temperature of the blank to 500°C at a rate of 10°C / min and keep it for 1 hour; then raise the temperature to 1300°C at a rate of 5°C / min and keep it for 30 minutes; then raise the temperature to 1500°C at a rate of 2°C / min and keep it for 2 hours; After the heat preservation is completed, the temperature is lowered to room temperature at a rate of 5°C / min to obtain the alumina-based ceramic body.
6. A high-strength alumina-based porcelain insulator according to claim 5, characterized in that: The mass percentage of ammonium citrate in the aqueous solution of ammonium citrate is 2%, and the mass of sodium alginate added is 1 / 10 of the mass of industrial alumina powder in the raw material components.
Citation Information
Patent Citations
Fiber, fiber aggregate and adhesive having the same
CN102677202A
High-thermal-conductivity type zirconia fiber-carbon nanotube reinforced alumina-based ceramic for PCB (printed circuit board) and preparation method of alumina-based ceramic
CN107151146A